HUBUNGAN KADAR GULA DARAH SEWAKTU DENGAN NEUROPATI DIABETIK PADA PASIEN DIABETES MELITUS TIPE 2 - Lisa, Mei; Lipinwati, Lipinwati; Istarini, Attiya; Syauqy, Ahmad; Shafira, Nyimas Natasha Ayu (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
ABSTRACT Introduction: Diabetes mellitus can cause microvascular complications, one of the most common being neuropathy, which is triggered by persistent hyperglycemia. Aims: To determine the relationship between random blood glucose levels and the incidence of diabetic neuropathy in Type 2 Diabetes Mellitus patients. Methods: This analytical observational study used a cross-sectional design involving 92 Type 2 Diabetes Mellitus patients. Neuropathy was assessed using the DNS-Ina questionnaire, while random blood glucose levels were obtained through laboratory tests. Data were analyzed using the Chi-square test. Results: Among the respondents, 53.3% did not experience hyperglycemia, while 82.3% had diabetic neuropathy. The Chi-square test revealed a p-value of 0.017 with an odds ratio of 4.568, indicating a significant association between random blood glucose levels and diabetic neuropathy. Conclusion: There is a significant relationship between random blood glucose levels and the incidence of diabetic neuropathy in Type 2 Diabetes Mellitus patients at H. Abdul Manap Regional Hospital, Jambi City. Keywords: diabetic neuropathy, random blood glucose, Type 2 diabetes mellitus